Penyuluhan Kesehatan Mental Pada Siswa/Siswi SMPN 02 Sawah Lunto - Sari Mariati; Aidil Rizki; Afiifah Kaltsum; Genta Buana Putra; Feby Elmira; Rivaldo, Rivaldo (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Mental health awareness among teenagers is crucial, as this developmental phase is filled with various emotional and social challenges. This activity aimed to enhance students' understanding of the importance of mental health and strategies to manage it. The method used was an educational approach through counseling sessions, interactive discussions, and Q&A sessions. The results showed that although initial student enthusiasm was low, as the session progressed, they became more engaged and actively participated in discussions. The use of rewards and ice-breaking sessions also contributed to increasing student participation. This counseling initiative is expected to help students better understand the significance of mental health and develop appropriate coping strategies.